Pre-adoption training: Experiences and recommendations from adoptive parents and course trainers. (December 2018) - Bergsund, Hans Bugge; Drozd, Filip; Hansen, Marit Bergum; Jacobsen, Heidi
Abstract: Adoptive parents experience a great number of challenges throughout the adoption process. Hence, there is a need for thorough preparation of prospective adoptive parents prior to them receiving a child into their family. This study aimed to evaluate a Norwegian pre-adoption course from the view of both adoptive parents and trainers. Participants were 10 adoptive parents and six trainers. Focus groups and semi-structured SWOT interviews were used for the parents and trainers, respectively. Thematic analysis was used as a framework for analyzing the interview data. The course was described in terms of various strengths and weaknesses, concerning the course framework, content, administrative support and informants' personal experiences. Multiple suggestions for improving the course were suggested, such as updating the course material, providing trainers with regular updates and ensuring a nuanced presentation of the material. Participants also reported a need for post-adoptive services and had various suggestions for what this kind of service should be like, whether it be a continuation of the pre-adoption course, a maternity or support group, or a resource center for adoptive families. These findings are in line with previous research, showing that adoptive families need specialized support that is suited to their unique situation. Highlights: A qualitative study to evaluate a pre-adoption training course Study participants were adoptive parents and course trainers Both groups reported the social aspect as one of the most useful aspects of the course Participants viewed the competency of course trainers as highly beneficial, but described the course as outdated and overly focused on the negative aspects of adoption Trainers were concerned about the lack of administrative support